A Rare Case of Mediastinal Bronchogenic Cyst Infected by Salmonella enteritidis - Jasleen Kaur; Philip J. McDonald; Ravinder D. Bhanot; Reda A. Awali; Sorabh Dhar; James Rowley (Case Reports in Pulmonology)
Bronchogenic cysts are rare congenital malformations which arise from abnormal budding of the primitive tracheobronchial tube and can localize to either the mediastinum or lung parenchyma. They remain clinically silent in most adults unless they become infected or are large enough to compress adjacent structures. Infections involving bronchogenic cysts are often polymicrobial. Gram-positive, Gram-negative, and mycobacterial infections have been reported, though frequently a pathogen is not identified. We present the case of a 46-year-old female with known history of bronchogenic cyst who presented with suspected postobstructive pneumonia. She underwent cyst excision with culture positive for Salmonella enteritidis, an extremely rare finding on review of the literature. The patient recovered following a three-week course of antibiotics for extraintestinal salmonellosis.